Associations Between Child Maltreatment and Depressive Symptoms Among Chinese College Students: An Analysis of Sex Differences - Chen, Xiaoliang; Zhang, Sheng; Huang, Guoliang; Xu, Yan; Li, Qian; Shi, Jingman; Li, Wenyan; Wang, Wanxin; Guo, Lan; Lu, Ciyong (Frontiers in Psychiatry, 2021)
Background: Depressive symptoms and child maltreatment are both global public health problems among young adults. This study aimed to investigate the associations between five types of child maltreatment and depressive symptoms among Chinese college students, with a focus on potential sex differences. Methods: A cross-sectional study of a nationally representative sample of Chinese college students was conducted from March to June 2019 with a multistage, stratified cluster, random sampling method. In total, 30,179 college students from 60 colleges of 10 Chinese province-level regions completed standard questionnaires, including a history of child maltreatment and current depressive symptoms. Results: The prevalence of depressive symptoms among college students in China was 7.3%. After adjusting for control variables, physical abuse (adjusted odds ratio [aOR]=1.20, 95% confidence interval [CI]=1.17-1.23), emotional abuse (aOR=1.21, 95% CI=1.19-1.23), sexual abuse (aOR=1.19, 95% CI=1.16-1.22), physical neglect (aOR=1.14, 95% CI=1.12-1.16) and emotional neglect (aOR=1.08, 95% CI=1.07-1.09) were all positively associated with depressive symptoms. Notably, a cumulative effect of child maltreatment on depressive symptoms among Chinese college students was observed. Moreover, sex differences in the associations of emotional abuse, emotional neglect, and the number of maltreatment types with depressive symptoms were statistically significant (P<0.05). Further stratification analyses showed that female students who experienced emotional abuse and emotional neglect had a higher risk of depressive symptoms than male students, and the cumulative effect of maltreatment types was stronger for females than males. Conclusion: Five types of child maltreatment and their co-occurrence were associated with an increased risk of depressive symptoms among college students. Furthermore, the effects of emotional abuse, emotional neglect and the number of maltreatment types on depressive symptoms were stronger for females than for males. These findings can promote understanding of the effects of child maltreatment on depressive symptoms, and prevention and intervention strategies for depressive symptoms should consider the type of child maltreatment and sex differences.